2000
DOI: 10.1111/1467-9450.00194
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effect of job involvement and organizational commitment on job turnover revisited: A note on the mediating role of turnover intention

Abstract: This study extends previous theoretical and empirical research on Blau and Boal's (1987) model of the interactive effect of job involvement and organizational commitment on employee withdrawal. Using longitudinal data from a survey among the nursing staff of a Swedish emergency hospital (N = 535) and register information on actual turnover, the results showed, in contrast to the statement of the original theoretical model, that turnover intention mediates the additive and multiplicative effects of job involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
158
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(169 citation statements)
references
References 25 publications
6
158
0
5
Order By: Relevance
“…Other empirical studies confirm the important role of organizational commitment in the turnover process (Baroudi, 1985;Blau & Boal, 1987;Cotton & Tuttle, 1986;Sjoberg & Sverke, 2000). It has also been reported that organizational commitment is more strongly related to turnover intention than job satisfaction (Baroudi, 1985).…”
Section: Theoretical Backgroundmentioning
confidence: 71%
“…Other empirical studies confirm the important role of organizational commitment in the turnover process (Baroudi, 1985;Blau & Boal, 1987;Cotton & Tuttle, 1986;Sjoberg & Sverke, 2000). It has also been reported that organizational commitment is more strongly related to turnover intention than job satisfaction (Baroudi, 1985).…”
Section: Theoretical Backgroundmentioning
confidence: 71%
“…Finally, the measure of student's 'intention to leave university' is perceptual, and may not represent the totality of student attrition. That noted, the efficacy of this measure in predicting eventual leave/exit is well documented (Sjoberg and Sverke 2000;Tett and Meyer 1993), though not within the context of university attrition. Future replication of the study herein, incorporating additional variables such as eventual turnover and other contextual control variables, is thus suggested.…”
Section: Limitationsmentioning
confidence: 99%
“…Blau ve Boal'ın bir uygulamasında, işe katılımın geliştirilmesi zor olduğunda, örgüte bağlılık yaratma çabalarının işgücü devrini azaltmada önemli hale geleceği ortaya konmuştur (Sjoberg ve Sverke, 2000).…”
Section: öRgütsel Bağlılık Kavramıunclassified